2020
DOI: 10.1177/0885066620979622
|View full text |Cite
|
Sign up to set email alerts
|

Fever in the ICU: A Predictor of Mortality in Mechanically Ventilated COVID-19 Patients

Abstract: Purpose: While fever may be a presenting symptom of COVID-19, fever at hospital admission has not been identified as a predictor of mortality. However, hyperthermia during critical illness among ventilated COVID-19 patients in the ICU has not yet been studied. We sought to determine mortality predictors among ventilated COVID-19 ICU patients and we hypothesized that fever in the ICU is predictive of mortality. Materials and Methods: We conducted a retrospective cohort study of 103 ventilated COVID-19 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 34 publications
4
31
3
Order By: Relevance
“…Some results were in line with published data, and some results were unexpected. For example, in contrast to data published by Choron et al, fever was no predictor of higher mortality in our study (9). A possible reason for this seeming discrepancy may be different de nitions of fever.…”
Section: Univariate Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…Some results were in line with published data, and some results were unexpected. For example, in contrast to data published by Choron et al, fever was no predictor of higher mortality in our study (9). A possible reason for this seeming discrepancy may be different de nitions of fever.…”
Section: Univariate Analysiscontrasting
confidence: 99%
“…Lactate, chloride, and paCO 2 , however, did not signi cantly differ in a relevant matter between the two groups. Choron et al found acidosis to be a predictor of mortality in mechanically ventilated COVID-19 patients (9).…”
Section: Univariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that fever is a predictor of poor prognosis in COVID-19 patients. 6,7,41 In our study, the patients included are all moderate patients, and there was no significant difference in the survival rate and hospital length of stay of patients with fever and without fever, which may be due to the limitation of sample size and the composition of different regions and populations. However, we subsequently followed up 55 of the above 187 patients at three months after discharge, and found that COVID-19 patients with fever in the acute phase had a higher proportion of persistent symptoms at three months after discharge, especially myalgia, which was significant difference in the two groups (54.5% vs 9.1%, p=0.018) (unpublished data).…”
Section: Discussionmentioning
confidence: 68%
“…Almost all COVID-19 patients had high fevers, some as high as 40°C, which might have contributed to CO 2 accumulation. A recent retrospective analysis has connected fever of COVID-19 patients on admission to worse outcome 22 . Aggressive medical treatment of hyperthermia could limit respiratory drive and improve CO 2 clearance in both awake and intubated patients.…”
Section: Discussionmentioning
confidence: 99%